Caracterização genética e do solo em populações nativas de Vochysia bifalcata warm. no Espírito Santo - Vianna, Larissa Souza (2015)
Vochysia bifalcata is popularly known as Guaricica, is a tree neotropical species whose survival is threatened due to degradation processes of the natural environment and man operation, considered the threat of state they are in, it is necessary to obtain more detailed information the genetic diversity of natural populations of this species, which is possible from studies with microsatellite markers. In this context, the present study was to evaluate objetvo the genetic diversity of Vochysia bifalcata species and characterize soil fertility in two native populations established in Caparaó National Park, ES. Therefore, leaf samples from 28 adult individuals were collected from two native populations of V. bifalta. For transferability test were tested 8 microsatellite primers developed for Qualea grandiflora and 10 designed to Vochysia ferruginea in the genome of individuals to V. bifalcata. Total genomic DNA was isolated using the Doyle & Doyle protocol (1990) modified. The amplified fragments were separated by electrophoresis on gel polyacrylamide 10% with 1X TBE buffer. Electrophoresis was performed at constant voltage of 100 W for 5 hours. The markers that generate satisfactory amplifications were then used for the studies and genetic diversity of structure in all 28 individuals sampled. We randomly selected six soil sampling points in each population at depths 0-5; 5-10 e 10-20 cm and chemical analyzes were performed using the methodology proposed by EMBRAPA (1997). The heterologous amplification results for V. ferruginea to V. bifalcata were satisfactory, and then used for statistical analysis and Q. grandiflora for V. bifalcata were satisfactory, however proved to be monomorphic. For starters, V. ferruginea the results showed the average occurrence of 4.85 lleles/locus. In both two populations of seven loci analyzed suggested the presence of null alleles, with significant frequency. The allelic richness were similar between the two populations. The average observed heterozygosity for the population I was 0.434 and population II was 0.355, both distinct from the expected to the Hardy-Weinberg equilibrium. The average fixation index for the population I was 0.390 and the population II was 0.328, indicating the presence of inbreeding within populations. The average value of Polymorphic Information Content (PIC) was 0.608 for the population I and 0.566 for the population II and are considered highly informative. The pair of genotypes (9 and 11) and (5 and 9) were identified as the least dissimilar opulations the population I and II, respectively. The amount of GST (0.079) indicated a moderate genetic differentiation among populations. To AMOVA, 92.86% of the variation was within 12 populations and among populations 7.13%. After analyzing the program, STRUCTURE was possible to define the division into two groups of genotypes. The obtained average gene flow was 2.88 being considered high enough to counteract the effects of genetic drift. These data generate important information about the genetic variability, proving the importance of Caparaó National Park for the species conservation. Soil samples analyzed demonstrated that the fertility of both populations are present and a low acidity, the homogeneity of the soil fertility can be explained by the soil and climatic characteristics similar between the two study populations.